2018
DOI: 10.18632/oncotarget.24382
|View full text |Cite
|
Sign up to set email alerts
|

Breast and ovarian cancer penetrance of BRCA1/2 mutations among Hong Kong women

Abstract: Germline mutations in BRCA1 and BRCA2 (BRCA1/2) are associated with increased risk of breast and ovarian cancer. The penetrance of breast and ovarian cancer in BRCA1/2 mutation carriers has been well characterized in Caucasian but not in Asian. Two studies have investigated the breast cancer risk in Asian women with BRCA1/2 mutations, and no published estimates are available for ovarian cancer. Therefore, we estimated the age-specific cumulative risk of BRCA1/2-associated breast and ovarian cancer in Chinese w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
(40 reference statements)
0
8
0
2
Order By: Relevance
“…Women with germline BRCA mutations have extremely high lifetime risks of developing breast and ovarian cancers [4][5][6][7]. Previous studies have shown that the cumulative incidence of breast cancer for BRCA1 and BRCA2-mutation carriers by 80 years old was about 72% [con dence interval (CI) 65% -79%] and 69% (61% -77%), respectively [7]. More speci cally, reports from Asian BRCA studies revealed that BRCA1 and BRCA2 mutation carriers have a 49-54% and 35-48% chance of developing breast cancer, respectively [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women with germline BRCA mutations have extremely high lifetime risks of developing breast and ovarian cancers [4][5][6][7]. Previous studies have shown that the cumulative incidence of breast cancer for BRCA1 and BRCA2-mutation carriers by 80 years old was about 72% [con dence interval (CI) 65% -79%] and 69% (61% -77%), respectively [7]. More speci cally, reports from Asian BRCA studies revealed that BRCA1 and BRCA2 mutation carriers have a 49-54% and 35-48% chance of developing breast cancer, respectively [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the cumulative incidence of breast cancer for BRCA1 and BRCA2-mutation carriers by 80 years old was about 72% [con dence interval (CI) 65% -79%] and 69% (61% -77%), respectively [7]. More speci cally, reports from Asian BRCA studies revealed that BRCA1 and BRCA2 mutation carriers have a 49-54% and 35-48% chance of developing breast cancer, respectively [6,7]. The risk of recurrent or contralateral breast cancer (CBC) also signi cantly increases in BRCA mutation carriers compared to non-BRCA carrier patients [4,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…With some congruence, breast and gynecological cancers, especially ovarian cancer, have been reported to be related to each other owing to their similar genetic basis (27), while a patient with breast cancer was later found to have primary ovarian small cell carcinoma and endometrioid adenocarcinoma of the uterus (28). Indeed, an increased risk of breast and ovarian cancers has been reported to be associated with germline mutations in BRCA1 and BRCA2 (29). This led us to investigate the role of α-mangostin in SKOV-3 ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…En las familias con un historial de cáncer de ovario o de mama, las mutaciones BRCA son responsables de aproximadamente el 90% de los casos de cáncer de ovario. El riesgo estimado de cáncer de ovario es del 39% en los portadores de mutaciones BRCA1 y del 17% en los portadores de mutaciones BRCA2 (8).…”
Section: Fisiopatologíaunclassified
“…Las pacientes deben someterse a un examen físico completo, incluido un examen recto vaginal con la vejiga vacía para evaluar las masas pélvicas y abdominales. En el examen recto vaginal, se debe evaluar los signos de disfunción endocrina, síndromes para neoplásicos y enfermedad metastática, incluyendo linfadenopatía inguinal (7,8).…”
Section: Cuadro Clínicounclassified